"Water-in-salt" electrolyte enhanced high voltage aqueous supercapacitor with carbon electrodes derived from biomass waste-ground grain hulls. Issue 58 (25th September 2020) - Pang, Mingjun; Jiang, Shang; Zhao, Jianguo; Zhang, Sufang; Wang, Runwei; Li, Ning; Liu, Rui; Pan, Qiliang; Qu, Wenshan; Xing, Baoyan
Abstract : To design high specific surface area and optimize the pore size distribution of materials, we employ a combination of carbonization and KOH activation to prepare activated carbon derived from ground grain hulls. Abstract : To design high specific surface area and optimize the pore size distribution of materials, we employ a combination of carbonization and KOH activation to prepare activated carbon derived from ground grain hulls. The resulting carbon material at lower temperature (800, BSAC-A-800) exhibits a porous structure with a high specific surface area of 1037.6 m 2 g −1 and a pore volume of 0.57 m 3 g −1 . Due to the synergistic structural characteristics, BSAC-A-800 reveals preferable capacitive performance, showing a specific capacitance as high as 313.3 F g −1 at 0.5 A g −1, good rate performance (above 73%), and particularly stable cycling performance (99.1% capacitance retention after 10 000 cycles at a current density of 10 A g −1 ). More importantly, the assembled symmetric supercapacitor using a water-in-salt electrolyte (17 m NaClO4 ) with high discharge specific capacitance (59 F g −1 at 0.5 A g −1 ), high energy density (47.2 W h kg −1 ) and high voltage (2.4 V) represents significant progress towards performance comparable to that of commercial salt-in-water electrolyte supercapacitors (with discharge specific capacitance of 50 F g −1, energy densities of ∼28.1 W h kg −1 and voltages of 2.0 V).